2020
DOI: 10.3389/fphys.2020.00305
|View full text |Cite
|
Sign up to set email alerts
|

Isoproterenol-Dependent Activation of TRPM7 Protects Against Neurotoxin-Induced Loss of Neuroblastoma Cells

Abstract: Neuronal function and their survival depend on the activation of ion channels. Loss of ion channel function is known to induce neurodegenerative diseases such as Parkinson's that exhibit loss of dopaminergic neurons; however, mechanisms that could limit neuronal loss are not yet fully identified. Our data suggest that neurotoxinmediated loss of neuroblastoma SH-SY5Y cells is inhibited by the addition of βadrenergic receptor (β-AR) agonist isoproterenol. The addition of isoproterenol to SHSY-5Y cells showed inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In this study, injection of antitumor carvacrol was found to reduce TRPM7 activity, thereby suppressing tumor growth in the mouse bladder cancer in vivo . Sun and his collaborators recently reported that apoptotic neuronal cell death induced by a Parkinson’s disease-related neurotoxin, MPP + , is protected by TRPM7 activation induced by isoproterenol ( Sun et al, 2020a ) and by TRPM7 overexpression ( Sun et al, 2020b ) in dopaminergic differentiated neuroblastoma SH-SY5Y cells. Moreover, in their in vivo studies, treatment with the neurotoxin, MPTP, was found to cause apoptotic tissue damage together with reduction of the TRPM7 level in mouse substantia nigra pars compacta (SNpc) region ( Sun et al, 2020b ).…”
Section: Roles Of Trpm2 and Trpm7 In Cell Volume Regulation And Cell ...mentioning
confidence: 99%
“…In this study, injection of antitumor carvacrol was found to reduce TRPM7 activity, thereby suppressing tumor growth in the mouse bladder cancer in vivo . Sun and his collaborators recently reported that apoptotic neuronal cell death induced by a Parkinson’s disease-related neurotoxin, MPP + , is protected by TRPM7 activation induced by isoproterenol ( Sun et al, 2020a ) and by TRPM7 overexpression ( Sun et al, 2020b ) in dopaminergic differentiated neuroblastoma SH-SY5Y cells. Moreover, in their in vivo studies, treatment with the neurotoxin, MPTP, was found to cause apoptotic tissue damage together with reduction of the TRPM7 level in mouse substantia nigra pars compacta (SNpc) region ( Sun et al, 2020b ).…”
Section: Roles Of Trpm2 and Trpm7 In Cell Volume Regulation And Cell ...mentioning
confidence: 99%
“…Transient receptor potential melastatin (TRPM) 7, a ubiquitously expressed ion channel coupled with an α kinase domain, is essential in maintaining intracellular Mg concentrations [83]. It has a role in neurodevelopment at early embryonic stages and coordinates the maturation of neuronal networks at later postnatal stages [84] and the loss of this channel is involved in the onset of neurological diseases [85]. At the cellular level, TRPM7 controls the proliferation and differentiation of neuronal cells and regulates the growth and migration of astrocytes [8].…”
Section: Magnesium and Alzheimer's Diseasementioning
confidence: 99%
“…Looking at TRPM7, it has been proposed as a candidate susceptibility gene for familial Parkinson's disease [108]. TRPM7 has a fundamental role in the survival of dopaminergic human neuroblastoma SH-SY5Y cells [109], and the suppression of TRPM7 inhibits Mg content and mitochondrial function, inducing cell death [85]. On the contrary, in an experimental model of Parkinson's disease induced by 6-hydroxy-dopamine, the total amounts of TRPM7 are increased [110], and the silencing TRPM7 is neuroprotective in pheochromocytoma PC12 cells [111].…”
Section: Magnesium and Parkinson's Diseasementioning
confidence: 99%
“…In the process of brain and myocardial injury, the increased expression of TRPM7 leads to the apoptosis of neurons and cardiomyocytes, while inhibition of TRPM7 can alleviate the stroke and myocardial injury. 18 , 19 However, the expression of TRPM7 in renal ischemia‐reperfusion injury has not been reported in detail. Therefore, this study established a rat model to explore the role of TRPM7 in rat renal ischemia‐reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…As an ion channel, TRPM7 can nonselectively allow the passage of divalent cations such as calcium and magnesium, thereby depolarizing excitatory cells and leading to intracellular calcium overload; as a kinase, TRPM7 can phosphorylate itself or activate its substrates Annexin AI (AnnexinI1, myosin II and m‐calDain 15–17 ). In the process of brain and myocardial injury, the increased expression of TRPM7 leads to the apoptosis of neurons and cardiomyocytes, while inhibition of TRPM7 can alleviate the stroke and myocardial injury 18,19 . However, the expression of TRPM7 in renal ischemia‐reperfusion injury has not been reported in detail.…”
Section: Introductionmentioning
confidence: 99%